Development of Optimization Model of Budget Allocation for Promotion of Unmanned Aerial Vehicles - Anatolievna Burdina, Anna; Nikolaevna Kaloshina, Marina; Timofeevna Manaenkova, Elena; Alexandrovna Nehrest, Anna; Mikhailovna Rogulenko, Tatyana (International Journal of Engineering and Technology, 2018)
This article discusses manufacturers of unmanned aerial vehicles, convex and stochastic programming, quantile optimization in economy are reviewed. Problem of budget allocation for promotion of engineering products is defined and solved in two variants: deterministic formulation, when a company is new and has not its own statistic data, and, otherwise, stochastic formulation. These problems were solved using methods of optimization theory and theory of stochastic systems such as simplex method, successive quadratic programming, and confidence method. Optimization model of budget allocation for promotion of unmanned aerial vehicles has been developed which optimizes budget for innovative engineering products.Â Â